The relevance of body positioning and its training effect on badminton smash - Li, S.; Zhang, Z.; Wan, B.; Wilde, B.; Shan, G. (Journal of Sports Sciences, 2017)
One of the dominant skills in badminton is the forehand overhead smash, which consists of 1/5 attacks during games. Empirical evidences show that one has to adjust the body position in relation to the coming shuttlecock to produce a powerful and accurate smash. Therefore, positioning is a fundamental aspect influencing smash quality. Unfortunately, a search of literature has shown that there is a dearth/lack of study on this fundamental aspect. The goals of this study were to determine the influence of positioning and training experience on smash quality in order to discover information that could help learn/acquire the skill. Using 3D motion capture and full-body biomechanical modelling, 14 skilled and 15 novice players were analysed. Results have revealed that the body positioning has direct influence on shuttlecock release angle and clearance height of the offensive player. The results also suggest that, for training the positioning of beginners, one could conduct a self-selected comfort position towards a statically hanged shuttlecock and then step one foot back - a practical reference marker for learning. As one gains experience through repetitive training, improved limbs` coordination would increase smash quality further. We hope our findings will benefit practitioners for developing effective training programmes for beginners.